Features of Judicial Law-Making in the Russian Federation and Its Acts: General Theoretical Aspect - Vladimir Valentinovich Kozhevnikov; Muhammad Ridwan (Polit Journal Scientific Journal of Politics, 2025)
The scientific article analyzes various features of judicial law-making from the perspective of its supporters, as well as the objective and subjective reasons for its occurrence in the Russian Federation. In the context of this article, the controversial issue of acts of judicial lawmaking is considered. Particular attention is focused on the concept and features of the legal positions of the Constitutional Court of the Russian Federation.